2007
DOI: 10.1007/s10916-007-9112-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Motion Artifacts Reduction Using 3-axis Accelerometer in E-textile ECG Measurement System

Abstract: The electro-conductive fabric (e-textile or e-fabric) as an electrode for ECG measurement is one of the best application for ubiquitous healthcare system. However, it is difficult to measure the bio-signal due to its sensitivity variation caused by impedance change, especially by motion of the subject. In this paper, adaptive motion artifacts reduction using motion information from 3-axis accelerometer is proposed and analyzed in quantitative manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…Compared to various motion artifact reduction systems [6], [7], [18], [19], where multiple ECG leads or signals other than the ECG need to be stored, the memory efficiency is retained. The proposed reconstruction algorithm that simply inverts the offset shift is not lossless mainly due to the non-linearity error of the DAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to various motion artifact reduction systems [6], [7], [18], [19], where multiple ECG leads or signals other than the ECG need to be stored, the memory efficiency is retained. The proposed reconstruction algorithm that simply inverts the offset shift is not lossless mainly due to the non-linearity error of the DAC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the MC simulations, the synthetic ECG signal analysis and selected in vivo measured ECG signal segments showed that the BWT prevents signal saturation episodes due to high baseline wander or motion artifacts. This is a clear advantage compared to more complex methods like adaptive filtering [6], [7], [18], [19] or source separation techniques [21] that filter the ECG in real-time but do not strictly avoid signal saturation. Thus, the relevant step towards high accurate long-term signals without major ECG data losses as were observed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Different varieties of adaptive filters have been applied to this problem including least mean squares (LMS) [7]- [9], recursive least squares (RLS), [10], [11], normalized LMS (NLMS) [12], and normalized signed regressor LMS [13]. Despite the popularity of adaptive filters, there is a disadvantage associated with them.…”
Section: Introductionmentioning
confidence: 99%
“…Patel et al [5] presents a more broader review of the wearable systems in home rehabilitation and early detection of disorders in health applications. The use of accelerometer sensors for removing motion artifacts in the wearable ECG sensor has been discussed in [12].…”
Section: Introductionmentioning
confidence: 99%